Menumbuhkan Kepekaan Lingkungan Siswa melalui Pembelajaran Sejarah Terkait Dampak Eksploitasi Alam Masa Revolusi Industri - Setianingsih, Sarah (Lembaga Yasin AlSys, 2023)
Humans will always depend on the environment. The environment is where living things live. Thus the need to protect the environment for the survival of living things around it. Concern for and sensitivity to the environment must be cultivated from an early age in order to maintain the survival of humans, animals and plants, as well as to preserve nature for the future. Growing environmental sensitivity can be integrated through learning in schools, one of which is learning history. By studying history, it will give students an understanding of the importance of the past as a form of awareness in the present and the future. One of the themes that can be raised in learning history is the industrial revolution, how this revolution caused changes in human life, but in fact had a bad impact on the environment, such as the exploitation of nature.